2021
DOI: 10.1021/acsestengg.1c00180
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Reaction Mechanisms and Functional Materials for Elemental Mercury Removal from Industrial Flue Gas

Abstract: Gaseous elemental mercury (Hg0) is of increasing concern in industrial flue gases because of its difficult disposal. Currently, catalysis conversion and adsorption to oxidized species (Hg2+) and particle-bonded states (Hgp) are two common Hg0 disposal methods. While no clear boundary exists between these methods, the selection of technologies for practical applications highly depends on the gas temperature, mercury concentration, and gas components over a solid material. This review aims to describe some princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 213 publications
0
13
0
Order By: Relevance
“…However, to date, there are few reported sorbents that can simultaneously remove Hg 0 and Hg 2+ . Commonly, the bonding stability and reaction rate between sulfur with Hg 0 and Hg 2+ highly depend on sulfur forms (S 2– , S 1– , S n 2– , and S 0 ). , Thus, the efficient route to enhance the performance of sulfur-based materials is generally to activate the sulfur sites by adjusting the coordination environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, there are few reported sorbents that can simultaneously remove Hg 0 and Hg 2+ . Commonly, the bonding stability and reaction rate between sulfur with Hg 0 and Hg 2+ highly depend on sulfur forms (S 2– , S 1– , S n 2– , and S 0 ). , Thus, the efficient route to enhance the performance of sulfur-based materials is generally to activate the sulfur sites by adjusting the coordination environment.…”
Section: Introductionmentioning
confidence: 99%
“…, Hg 2 SO 4 and HgO). Among them, mercury chalcogenides (HgS and HgSe) exhibited relatively higher thermostability and lower solubility . Notably, compared with HgS and HgSe, Hg 3 Se 2 Cl 2 had higher thermal stability and lower solubility in an acid solution.…”
Section: Resultsmentioning
confidence: 99%
“…Although chalcogen elements (O, S, or Se) could be used for Hg 0 uptake and stabilization, their field applications were seriously limited by the harsh flue gas conditions such as high temperature, high concentration of SO 2 , and water vapor , because the fluctuation of flue gas temperature may destroy the mercury–chalcogen bond, while SO 2 and H 2 O can occupy the Hg 0 adsorption sites and lead to surface Hg 2+ dissolution and re-emission . Obviously, the ultimate remediation goal is to separate Hg 0 from flue gas and simultaneously convert it to superstable states for safe storage, which has not been achieved as far as we know.…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental and theoretical studies have recently reported that metal sulfides have great tolerance to SO 2 . 23,24 Notably, Liu et al found that SO 3 would compete with Hg 0 for adsorption sites on the CuS surface. 25 Yang et al observed that SO 3 could oxidize HgS to HgSO 4 and was reduced to SO 2 .…”
Section: mentioning
confidence: 99%
“…The aim was to develop a material that can efficiently reduce SO 3 at a specific temperature and has a high resistance against coexisting flue gas components, especially high concentrations of SO 2 . Many experimental and theoretical studies have recently reported that metal sulfides have great tolerance to SO 2 . , Notably, Liu et al found that SO 3 would compete with Hg 0 for adsorption sites on the CuS surface . Yang et al observed that SO 3 could oxidize HgS to HgSO 4 and was reduced to SO 2 .…”
Section: Introductionmentioning
confidence: 99%